2016
DOI: 10.1049/iet-nbt.2015.0088
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro toxicity of carbon nanotube/polylysine colloids to colon cancer cells

Abstract: Single-walled carbon nanotubes (SWCNTs) are thoroughly purified and dispersed in an aqueous solution of high molecular weight poly-L-lysine (pLlys). Human intestinal epithelial Caco-2/TC7 cells are incubated with the SWCNT dispersions in pLlys, and their effects on cell viability are studied by image flow cytometry. No significant changes are observed in the cell culture wells up to pLlys concentrations of 10 μg ml. However, high mortality is detected at pLlys concentrations of 100 μg ml. The presence of oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In previous reports, we found that SWCNTs induced oxidative stress and altered the normal intestinal function in a rabbit model, even if SWCNTs were purified and wrapped in a hydrophilic dispersant, casting a serious concern on their hypothetical use as a drug vehicle to treat intestinal diseases. However, these adverse effects were mitigated if SWCNTs were purified by dispersion in poly­( l -lysine), as tested in vitro, thus showing the potential benefits of a proper surface modification of SWCNTs in the design of drug vehicles to treat diseases. In light of the promising behavior of both NCC types to stabilize SWCNTs in water in very different fashions, at this point, we focused on ascertaining the effects of such SWCNT–NCC hybrids on the viability of intestinal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, we found that SWCNTs induced oxidative stress and altered the normal intestinal function in a rabbit model, even if SWCNTs were purified and wrapped in a hydrophilic dispersant, casting a serious concern on their hypothetical use as a drug vehicle to treat intestinal diseases. However, these adverse effects were mitigated if SWCNTs were purified by dispersion in poly­( l -lysine), as tested in vitro, thus showing the potential benefits of a proper surface modification of SWCNTs in the design of drug vehicles to treat diseases. In light of the promising behavior of both NCC types to stabilize SWCNTs in water in very different fashions, at this point, we focused on ascertaining the effects of such SWCNT–NCC hybrids on the viability of intestinal cells.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, we found that SWCNTs induced oxidative stress and altered the normal intestinal function in a rabbit model, 47 even if SWCNTs were purified and wrapped in a hydrophilic dispersant, casting a serious concern on their hypothetical use as a drug vehicle to treat intestinal diseases. However, these adverse effects were mitigated if SWCNTs were purified by dispersion in poly(L-lysine), as tested in vitro, 48 thus showing With this purpose, we have carried out biological studies in Caco-2 human intestinal cells (colon epithelium), through the in vitro assessment of cellular viability using the MTT assay, which measures the mitochondrial ability to metabolize MTT by reduction. Viable cells with active metabolism convert MTT into a purple-colored formazan product.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The cytotoxicity observed at doses higher than 100 ng/mL was due to the active poly- l -lysine in the medium in which the CNTs were dispersed, and not because of the CNTs. The study indicated that CNTs were inert and acted as carriers for poly- l -lysine …”
Section: Resultsmentioning
confidence: 99%
“…The study indicated that CNTs were inert and acted as carriers for poly-L-lysine. 115 With respect to cytotoxicity on colorectal cancer cells in vitro, f SWCNT-COOH (0.4 μm−1.2 μm with an outer diameter of 15 ± 5 μm) was tested at the dose range of 5− 1000 μg/mL. Improved production of reactive oxygen species (ROS) as the underlying mechanism of cytotoxicity was observed only after 100 μg/mL.…”
Section: Inherent Properties Ofmentioning
confidence: 99%
“…Moreover, molecular transportation systems based on the chemical interaction between the CNT wall and the molecule encapsulated in the CNT or on translocation across the cell membrane and solubilisation have been designed [48, 49]. Experimental results [50] have revealed the usability of single‐walled CNTs as carriers in pharmacological formulations for the treatment of peptic tract diseases as well as the successful integration of CNTs with biomolecules. The incorporation of biomolecules within CNTs permits their use in hybrid communication systems as active field‐effect transistors and electrochemical biosensors (enzymatic, DNA sensors, or immune‐sensors).…”
Section: Cnts In Nanomedicine Applicationsmentioning
confidence: 99%